Bio-production of lactic and lactobionic acids using whey from the production of cow’s milk Wagashi cheese in Benin - Djobo, Oumarou; Sina, Haziz; Tagba, Souriatou; Ahyi, Virgile; Savadogo, Aly; Adjanohoun, Adolphe; Rendueles, Manuel; Baba-Moussa, Lamine (Frontiers in Nutrition, 2022)
Traditional cheese is the main milk derivative in Bénin. This traditional process is not efficient and generate a lot of whey which has no real use until now. It is just rejected without being environmentally treated. Its use as a source for lactobionic and lactic acids production by Pseudomonas taetrolens and Lactobacillus casei is studied in this work, being also a proposal that can greatly boost economically the dairy sector in the country and reduce the end-of-cycle impact of the residue. To our knowledge, no data is available in the metabolization of Bénin’s traditional cheese whey and its potential transformation into commercially valuable products such as lactobionic and lactic acids. With bulk filtration, non-controlled pH batch fermentations and without nutrients supplementation, 66% and 22% of lactose in the traditional cheese whey have been converted into lactobionic acid and lactic acid using Pseudomonas taetrolens and Lactobacillus casei respectively. Those are important results that encourage to enhance the bioprocesses used in a cost-effective way in order to scale up an industrial production.